PENERAPAN SISTEM ERP PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Susanti Susanti; Nova Susanti; Ahda Nadhira; Chairunnisah Chairunnisah; Oktiani Devanti Simarmata; Risye Arnetta Sumitro; Santi Santi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The use of technology in companies is growing rapidly every year. The system under development can quickly integrate all company data and generate supporting reports according to management needs. One system that can adapt to these conditions is the Enterprise Resource Planning (ERP) system. ERP design is an information pattern for manufacturing and service companies that serves to unify and automate business activities. ERP helps efficient business activities by combining business activities including sales, marketing, production, logistics, accounting, and human resources. The purpose of this study, namely to determine the effectiveness of ERP system implementation in manufacturing companies in developing and developed countries. In this study using the literature review method. The results of this study, namely the use of ERP systems have a positive impact on the company. Business management using an ERP system is more efficient in time and other resources, easier. ERP is very useful for companies in supporting their business processes so that they become organized and organized. An ERP or enterprise resource planning system is one way out for companies with high complexity businesses and especially companies that are already developing.